The complete mitochondrial genome of Chaetodon octofasciatus (Perciformes: Chaetodontidae) and phylogenetic studies of Percoidea - Zhu, Kehua (Mitochondrial DNA B Resour, 2018)
The complete mitochondrial genome of this species was first determined in this study, which is 16,485 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, a putative control region, and 1 origin of replication on the light-strand. The overall base composition includes C(28.2%), A(28.3%), T(27.4%), and G(16.1%). Moreover, the 13 PCGs encode 3796 amino acids in total, 12 of which use the initiation codon ATG except COI that uses GTG. Most of them have TAA as the stop codon, whereas ND3 ends with TAG, and three protein-coding genes (COII, ND4, and Cytb) ended with the incomplete stop codon represented as a single T. The phylogenetic tree based on the Neighbor Joining method was constructed to provide relationship within Percoidea, which could be a useful basis for management of this species.